Characterization of salA, syrF, and syrG Genes and Attendant Regulatory Networks Involved in Plant Pathogenesis by Pseudomonas syringae pv. syringae B728a - Vaughn, Vanessa L. (PLoS One, 2016)
Pseudomonas syringae pv. syringae B728a, causal agent of brown spot on bean, is an economically important plant pathogen that utilizes extracellular signaling to initiate a lifestyle change from an epiphyte to a pathogen. LuxR regulatory proteins play an important role in the transcriptional regulation of a variety of biological processes involving two-component signaling, quorum sensing, and secondary metabolism. Analysis of the B728a genome identified 24 LuxR-like proteins, three of which are encoded by salA, syrF, and syrG located adjacent to the syringomycin gene cluster. The LuxR-like proteins encoded by these three genes exhibit a domain architecture that places them in a subfamily of LuxR-like proteins associated with regulation of secondary metabolism in B728a. Deletion mutants of salA, syrF, and syrG failed to produce syringomycin and displayed reduction of virulence on bean. The transcriptional start sites of salA, syrG, and syrF were located 63, 235, and 498 bp upstream of the start codons, respectively, using primer extension analysis. The predicted -10/-35 promoter regions of syrF and syrG were confirmed using site-directed mutagenesis and GFP reporters that showed conserved promoter sequences around the -35 promoter region. Overexpression analysis and GFP reporters identified SyrG as an upstream transcriptional activator of syrF, where both SyrG and SyrF activate promoters of syringomycin biosynthesis genes. This study shows that syrG and syrF encode important transcriptional regulators of syringomycin biosynthesis genes.